CEO Pay Disparity, Takeover Premiums and Bidder Performance in Australia: Efficient Contracting or Managerial Power - Luong, Hoa; Duong, Lien; Evans, John (WILEY, 2021)
We compare acquiring firms’ CEO pay with that of the highest-paid non-CEO director and investigate the influence of CEO pay disparity on takeover premiums and bidder performance. Based on a takeover sample of Australian listed targets and bidders during the 2002–2015 period, we find that takeover premiums are significantly higher if the deals are processed by acquiring firms with higher CEO pay disparity. Although these firms do not receive favourable immediate market responses to their takeover announcements, they outperform in the long run. We find no evidence that offering a large takeover premium harms shareholders’ wealth. Overall, our findings largely support efficient contracting theory in the Australian M&A context.